TEMA DALAM NOVEL-NOVEL PERIODE BALAI PUSTAKA - Kasimbara, Devi Cintia; Wahyuningsih, Wahyuningsih; Setiawan, Kodrat Eko Putro (IdeBahasa, 2021)
Balai Pustaka is the initial period of the emergence of modern Indonesian literature, so it is necessary to know more about the novels that have become milestones in the history of the emergence of modern Indonesian literature. During this period, many novels emerged with stories that had various similarities. This prompted the writer to find out what themes dominated the novels published in this period. In this study, the authors took six novel samples, namely Azab and Sengsara by Merari Siregar, Sitti Nurbaya by Marah Rusli, Salah Asuhan by Abdoel Moeis, Looking for the Thief of Virgins by Suman Hs., and Dian Yang Takdir Alisjahbana by S. Takdir Alisjahbana. The theory Robert Stanton is used as an analytical knife. In this theory, Stanton focused more on how to identify the theme of a literary work, where the theme is an aspect of the story that is parallel to the 'meaning' in human experience; something that makes an experience so memorable. The results of this study could be seen that the themes raised in the novels of the Balai Pustaka period have similarities, namely traditional issues, forced marriages, and the conflict between the old and young groups so that these novels have similarities in the issues raised.